THE INFLUENCE OF GROUP GUIDANCE SERVICES WITH ASSERTIVITY CONTENT ON BULLYING BEHAVIOR IN CLASS X STUDENTS AT SMK NEGERI 3 PANYABUNGAN - Nur Fitri, Eka; Deliati, Deliati (Faculty of Tarbiyah nad Teacher Training, 2024)
This research aims to determine the effect of group tutoring services with assertive content on bullying behavior in class X students at SMK Negeri 3 Panyabungan. The type of research used in this research is experimental research by providing activities to the guidance of the experimental group. The researcher used 10 students as samples in this research. This research uses IBM SPSS Statistics 26. Based on the results of the t test, it can be seen that the significance level is 0.05 with a probability of 1-α and degrees of freedom dk = n-k= 10-1=9, so from the t table we get t = 2.262. Thus tcount>ttable (10.713 > 2.262) or Sig .000 < 0.05. Where the sig (2-tailed) value is smaller than 0.05 so it can be concluded that Ha is accepted and Ho is rejected. Ha was accepted because of the differences between the two tests.